Application of Cervical Vestibular-Evoked Myogenic Potentials in Adults with Moderate to Profound Sensorineural Hearing Loss: A Preliminary Study - Ciodaro, Francesco; Freni, Francesco; Alberti, Giuseppe; Forelli, Marco; Gazia, Francesco; Bruno, Rocco; Sherdell, Enrique Perello; Galletti, Bruno; Galletti, Francesco (International Archives of Otorhinolaryngology, 2020)
Introduction The cochlea and the vestibular receptors are closely related in terms of anatomy and phylogeny. Patients with moderate to profound sensorineural hearing loss (MPSHL) should have their vestibular organ functions tested.Objective To evaluate the incidence of vestibular abnormalities in patients with MPSHL and to study the correlation between the etiology of hearing loss (HL) and a possible damage to the labyrinth.Methods A case-control retrospective study was performed. In the case group, 20 adults with MPSHL of known etiology were included. The control group was composed of 15 adults with normal hearing. The case group was divided into 4 subgroups based on the etiology (bacterial meningitis, virus, vascular disease, congenital). Cervical vestibular-evoked myogenic potentials (cVEMPs) were used to rate the saccular function and lower vestibular nerve.Results The study was performed in 70 ears, and it highlighted the presence of early biphasic P1-N1 complex in 29 (71.5%) out of 40 ears in the study group, and in all of the 30 ears in the control group (p = 0.001). Regarding the presence or absence of cVEMPs among the four subgroups of patients with MPSHL, the data were statistically significant (p < 0.001). The comparison between the latencies and amplitude of P1-N1 in case and control groups from other studies and in the four subgroups of cases in the present study did not detect statistically significant differences.Conclusion The present study demonstrates that patients with MPSHL have a high incidence of damage to the labyrinthine organs, and it increases the current knowledge about the etiopathogenesis of sensorineural HL, which is often of unknown nature.
Keywords: hearing loss; bacterial meningitis; vestibular-evoked myogenic potentials